PENGENDALIAN BANJIR SUNGAI DOMBO SAYUNG KABUPATEN DEMAK - Arahman, Imam; Budiarjo, Imam; Darsono, Suseno; Sugiyanto, Sugiyanto (Jurnal Karya Teknik Sipil, 2015)
Flooding is one of the disasters that often occur in Demak Regency especially Sayung area, Karang Asem, and Mranggen. The impact of floods can not be ignored, such as damage to city infrastructure, and socio-economic losses in the region Demak regency occur due to inundation and inundation long time. Dombo Sayung River Flood Control Objectives is to reduce the occurrence of floodwaters in the area Demak regency using structural measures. The flood control study using a return period of 100 years. With a return period flood hydrograph Q100th Dombo Sayung River analyzed using HEC-HMS software. While the hydraulics analysis were analyzed using the HEC-RAS software. The analysis shows a cross-existing conditions Dombo Sayung River insufficient to drain the flood discharge Q100th of 343.0 m3/sec with the effect of the floods, so it needs to repair the river cross-section an attempt to enlarge the drainage of the river.